A study on hydrogen storage performance of Ti decorated vacancies graphene structure on the first principle. Issue 23 (14th April 2021) - Cui, Hong; Zhang, Ying; Tian, Weizhi; Wang, Yazhou; Liu, Tong; Chen, Yunjian; Shan, Pengyue; Yuan, Hongkuan
Abstract : The structural properties, formation energy, adsorption energy, and electronic properties of vacancy graphene are studied by first-principles analysis. Abstract : The structural properties, formation energy, adsorption energy, and electronic properties of vacancy graphene are studied by first-principles analysis. We found that the formation energy and adsorption energy of double vacancy graphene (DVG-4) are the largest. A single defect in DVG-4 can adsorb at least nine hydrogen molecules, and compared with Ti modified single vacancy graphene (SVG–Ti), the adsorption capacity is increased by 80%. When DVG-4 adsorbs the second, third, and fourth hydrogen molecules, the adsorption energy is greater than 0.7 eV, which is not conducive to the release. Density of state (DOS) and electron density difference (EDIFF) results reveal that charge transfer occurs among hydrogen molecules, Ti atoms, and DVG-4, decreasing the hydrogen adsorption capacity of DVG-4 by 33%. DVG - 4 has the potential to become an excellent hydrogen storage material.